Effectiveness of Irrigation Methods and Time of Providing Water in Maintaining Soil Classification for Increasing Soybean Production - Aminah Aminah; Fadjry Djufry; Abdul Wahid Rauf; Saida Saida; Marliana S. Palad; Salim Salim (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
This study aimed to get the best irrigation method and determine the best time-effective provision of water to maintain optimum soil moisture for increase soybean crop production. This research was conducted in the field in Maros District, South Sulawesi. The experiment used a split-plot design and was repeated three times. The main plot was an irrigation method, namely the Scatter irrigation, Furrow, and Flood irrigations method, and its plot was the time of irrigation, namely every 15 days of age, at the period of 15 days, and full flowering and irrigation every 10 days. The results showed that the watering technique using the waterlogging method at the time at the age of 15 days and full flowering had the potential to increase the yield production of soybean, that was the number of pods 164.95 pieces, the weight of seeds 37.11 g, and production 4.64 t/ha. The inundation method was more effective in maintaining soil moisture and twice the application time. But in an optimal amount (229 l/time) was very effective in maintaining soil moisture.